Teach Aquaculture Curriculum: Fish-Eating Contest - Amber L. Garr; Cortney L. Ohs; Brian E. Myers; Craig S. Kasper; R. Leroy Creswell; Frank A. Chapman; Carlos V. Martinez; Elisa J. Livengood (EDIS, 2010)
FA169, a 4-page activity by Amber L. Garr, Cortney L. Ohs, Brian E. Myers, Craig S. Kasper, R. Leroy Creswell, Frank A. Chapman, Carlos V. Martinez, and Elisa J. Livengood, is activity 2 of the Teach Aquaculture Curriculum. In this activity for grades 5-12, students observe the external anatomy of fish to determine feeding behaviors and recommend an aquaculture diet based on their observations. Includes student performance standards. Published by the UF School of Forest Resources and Conservation, Program in Fisheries and Aquatic Sciences, May 2010.